An Analysis of Slang Words in Song Lyrics Used by Ariana Grande - I Gusti Ayu Agung Indah Jayanthi; Ni Wayan Suastini; I Gusti Agung Sri Rwa Jayantini (Universitas Teknokrat Indonesia, 2022)
The study concerns with the slang word in song lyrics. The aims of the study are focused on analyzing the types of slang proposed by the theory of Chapman (2007) and the effect of slang words by the theory by Eble (1996). The method of the research used descriptive qualitative method. The data got from song lyrics by Ariana Grande, the song titles were 34 + 35, Positions, Thank U, Next, and Side to Side. Data were obtained from the data collection through listening to the songs, reading the song, printing the song, underlining words containing the type and effect of slang words, and noting the data. The researcher found 21 (78%) data types of primary slang and 6 (22%) data types of secondary slang. The effects of slang words there are 21 (78%) slang words identified as expressing informality and 6 (12%) slang words identified as identifying group members and no slang found to apposed establishing authority.